Diagnostic Efficacy of Ultrasound, Cytology, and BRAFV600E Mutation Analysis and Their Combined Use in Thyroid Nodule Screening for Papillary Thyroid Microcarcinoma - Du, Jing; Han, Ruijun; Chen, Cui; Ma, Xiaowei; Shen, Yuling; Chen, Jun; Li, Fenghua (Frontiers in Oncology, 2022)
Background: Ultrasound, cytology and BRAFV600E mutation analysis were applied as valuable tools in the differential diagnosis of thyroid nodules. The aim of the present study was to evaluate the diagnostic efficiency of three methods and their combined use in screening for papillary thyroid microcarcinoma (PTMC). Methods: 1081 patients with 1157 thyroid nodules (0.5–1 cm in maximum diameter) classified as thyroid imaging reporting and data system (TIRADS) 4-5 were recruited. All the patients underwent ultrasound, fine-needle aspiration (FNA) examination and an additional BRAFV600E mutation test. TIRADS and Bethesda system for reporting thyroid cytopathology (BSRTC) were adopted to judge the ultrasound and cytological results. The receiver operating characteristic (ROC) curve was established to assess the diagnostic values of different methods. Results: Of the 1157 nodules, 587 were benign and 570 were PTMCs. BRAFV600E mutation test had highest sensitivity (85.4%), specificity (97.1%), accuracy (91.4%) and the area under the ROC curve (Az) value (0.913) among three methods. The combination of BSRTC and BRAFV600E mutation analysis yielded a considerably high sensitivity (96.0%), accuracy (94.3%) and negative predictive value (95.9%) than either BSRTC or BRAFV600E mutation alone (P < 0.0001 for all comparisons). Of all the methods, the combined use of three methods produced in the best diagnostic performance (Az = 0.967), which was significantly higher than that (Az = 0.943) for the combination of BSRTC and BRAFV600E mutation (P < 0.0001). The diagnostic accuracy of the molecular method in the 121 nodules with indeterminate cytology was 90.1% (109/121), which was significantly higher than that of TIRADS classification 74.4% (90/121) (P = 0.002). Conclusion: The combined use of ultrasound, cytology and BRAFV600E mutation analysis is the most efficient and objective method for diagnosing PTMC. Both BRAFV600E mutation and TIRADS classification are potentially useful adjuncts to differentiate thyroid nodules, especially indeterminate samples classified as BSRTC III.